Incorporating E-Learning Madrasah in Teaching Reading Practice - Mia Amalia; Nia Hoerniasih; Mobit Mobit (Jurnal Ilmiah Wahana Pendidikan, 2023)
The students learn independently during the Covid-19 pandemic and spend long periods of time at home. In order to prepare e-Learning Madrasah for use by Islamic schools in Indonesia, students are required to be taught online through specific Internet Platforms recommended by the Ministry of Religion. This study examines how teachers at the Islamic grade school of Karawang are incorporating e-Learning Madrasah as a media and students' responses to using e-Learning Madrasah in their reading comprehension process. Observation and interviews with teachers and students are used to collect the data. The results of these studies have shown that a number of responses suggest that the use of eLearning Madrasah does not work effectively in English, particularly with respect to teaching reading. Despite the fact that students are still enjoying using media provided by their school, during a Covid 19 pandemic they will be able to carry out educational activities